Global research on syndemics: a meta-knowledge analysis (2001-2020) [version 2; peer review: 2 approved] - Tasmiah Nuzhath; James N. Burdine; Banga Kamal Basu; Nobonita Saha; Helal Uddin Ahmed; Tamal Joyti Roy; Tahmina Tasnim Rodela; Md Mahbub Hossain; Ping Ma; Samia Tasnim; E. Lisako J. McKyer (F1000Research, 2023)
Background: Syndemics or synergies of cooccurring epidemics are widely studied across health and social sciences in recent years. Methods: We conducted a meta-knowledge analysis of articles published between 2001 to 2020 in this growing field of academic scholarship. Results: We found a total of 830 articles authored by 3025 authors, mostly from high-income countries. Publications on syndemics are gradually increasing since 2003, with rapid development in 2013. Each article was cited more than 15 times on average, and most (n = 604) articles were original studies. Syndemics research focused on several areas, including HIV/AIDS, substance abuse, mental health, gender minority stressors, racism, violence, chronic physical and mental disorders, food insecurity, social determinants of health, and coronavirus disease 2019. Moreover, biopsychosocial interactions between multiple health problems were studied across medical, anthropological, public health, and other disciplines of science. Conclusions: The limited yet rapidly evolving literature on syndemics informs transdisciplinary interests to understand complex coexisting health challenges in the context of systematic exclusion and structural violence in vulnerable populations. The findings also suggest applications of syndemic theory to evaluate clinical and public health problems, examine the socioecological dynamics of factors influencing health and wellbeing, and use the insights to alleviate health inequities in the intersections of synergistic epidemics and persistent contextual challenges for population health.